PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAN WISATAWAN MELALUI KUALITAS PELAYANAN (STUDI KASUS OBYEK WISATA KEPULAUAN SERIBU) - Sukarni Novita Sari (Majalah Ilmiah Bijak, 2016)
Tourism sector became strategic and significant when it taken seriously and done professionally. Selling tourism products and services need not only a coordination, but a good cooperation between all organizations that are responsible for developing tourism sector and all parties involved or associated with tourism activities. One effort that can be done is to develop a marketing strategy that is expected to attract tourists back and also can create self-satisfaction in tourists.To obtain optimal results, this marketing strategy has a broad scope in the field of marketing of which is a strategy in the face of competition, pricing strategy, product strategy, service strategy and so on. Therefore, this study will analyze about the influence of marketing strategies and quality of service to tourist satisfaction.The method used in this research is quantitative with the questionnaire as a data collection tool to obtain the responses of the respondents regarding the variables in this study. The data analysis technique used in this research is Structural Equation Modeling (SEM). Respondents involved in this study are 120 tourists that also customers of CV Ryzqi Samudra.The research proves that the marketing strategy has a positive and significant impact on the quality of services and satisfaction of tourists. Variable quality of service also has a positive and significant impact on tourist satisfaction.